What do Students Learn in the Numbers for Life Course at McMaster University? Assessing students’ improvement and retention of numeracy knowledge and skills - Goertz, Madison (My University, 2024)
Our society is surrounded by numbers and throughout our lifetime we all experience numeric situations daily. Developing necessary numeracy skills is a crucial part of being able to fully participate in modern technological society and engage in the world around us. The course Numbers for Life at McMaster University (Math 2UU3) is designed to teach about critical numeracy problems that we are faced with in our daily lives and is offered to non-mathematics major students in their second year or above. Students in the course were surveyed three times through a pre-test, post-test and delayed post-test, that was written one year after course completion. Using the responses to these survey instruments, this thesis focuses on studying the retention of a student's ability to understand numeric information and their ability to communicate their answers. Having good retention is key for a learner to successfully apply what they have learned in future real-life scenarios. By studying the retention of students' responses to commonly encountered real-world math problems, we can determine how valuable courses like Numbers for Life are to have in place for all students.